Brexit under Scrutiny in EU Member States: What Role for National Parliaments in Austria and Germany? - Meissner, Katharina Luise (2019)
Among national parliaments (NPs) in the EU, the Austrian Nationalrat and the German Bundestag stand out as strong legislatures in EU affairs. Both parliaments have used their rights to great extent in recent EU negotiations on international agreements such as the one with Canada on a Comprehensive Economic and Trade Agreement. Yet, in the negotiations with the UK their involvement varies. Why is this so? Scholarly work on Brexit so far focused on the European Parliament or the UK parliament, while attention to NPs in the EU27 is scarce. This article fills this void in research by tracing the Austrian and German parliaments’ activities in the Brexit negotiations. Despite similar institutional strength I find that the German Bundestag is more extensively involved, particularly on an informal level, compared to the Austrian Nationalrat. The reason for this is Brexit’s varying saliency in these two countries given their different levels of exposure to the UK’s withdrawal. As saliency of a policy issue is considered a major explanatory factor for why NPs engage in EU affairs, the results of this article confirm this expectation within the realm of EU international negotiations.